A synthesis method for cobalt doped carbon aerogels with high surface area and their hydrogen storage properties - Tian, Hu-Yong; Buckley, Craig; Sheppard, Drew; Paskevicius, Mark; Hanna, N. (Pergamon-Elsevier Science Ltd, 2010)
Carbon aerogels doped with nanoscaled Co particles were prepared by first coating activated carbon aerogels using a wet-thin layer coating process. The resulting metal-doped carbon aerogels had a higher surface area (1667 m2 g-1) and larger micropore volume (0.6 cm3 g-1) than metal-doped carbon aerogels synthesised using other methods suggesting their usefulness in catalytic applications. The hydrogen adsorption behaviour of cobalt doped carbon aerogel was evaluated, displaying a high w4.38 wt.% H2 uptake under 4.6 MPa at -196 C. The hydrogen uptake capacity with respect to unit surface area was greater than for pure carbon aerogel and resulted in 1.3 H2 (wt. %) per 500 m2 g-1. However, the total hydrogen uptake was slightly reduced as compared to pure carbon aerogel due to a small reduction in surface area associated with cobalt doping. The improved adsorption per unit surface area suggests that there is a stronger interaction between the hydrogen molecules and the cobalt doped carbon aerogel than for pure carbon aerogel.